2016
DOI: 10.1074/jbc.m115.684357
|View full text |Cite
|
Sign up to set email alerts
|

β-Arrestin-mediated Angiotensin II Signaling Controls the Activation of ARF6 Protein and Endocytosis in Migration of Vascular Smooth Muscle Cells

Abstract: Angiotensin II (Ang II) is a vasopressive hormone but is also a potent activator of cellular migration. We have previously shown that it can promote the activation of the GTPase ARF6 in a heterologous overexpressing system. The molecular mechanisms by which receptors control the activation of this small G protein remain, however, largely unknown. Furthermore, how ARF6 coordinates the activation of complex cellular responses needs to be further elucidated. In this study, we demonstrate that Ang II receptors eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 68 publications
(80 reference statements)
0
20
0
Order By: Relevance
“…β-arrestins were found to promote clathrin-mediated internalization of GPCRs by interacting with, and scaffolding various components of, the clathrin-mediated endocytosis machinery. In particular, β-arrestin2 promotes the activation of ARF6 and endocytosis in the migration of vascular smooth muscle cells [56]. After overexpression in mouse embryonic fibroblasts, β-arrestin2 also enhanced low density lipoprotein receptor (LDLR) endocytosis (by 65%), through the interaction between β-arrestin2 with LDLR cytoplasmic tail [57].…”
Section: Discussionmentioning
confidence: 99%
“…β-arrestins were found to promote clathrin-mediated internalization of GPCRs by interacting with, and scaffolding various components of, the clathrin-mediated endocytosis machinery. In particular, β-arrestin2 promotes the activation of ARF6 and endocytosis in the migration of vascular smooth muscle cells [56]. After overexpression in mouse embryonic fibroblasts, β-arrestin2 also enhanced low density lipoprotein receptor (LDLR) endocytosis (by 65%), through the interaction between β-arrestin2 with LDLR cytoplasmic tail [57].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from canonical G‐protein–mediated signaling, G‐protein–coupled receptors also activate a β‐arrestin–dependent noncanonical pathway 40. β‐Arrestins have been reported to be involved in motility of SMCs 41. We found that silencing of β‐arrestin2 with siRNA transfection in SMCs (Figure S3A) markedly reduced the phosphorylation of mTOR and p70S6K induced by BW723C86 (Figure 5B).…”
Section: Resultsmentioning
confidence: 70%
“…40 b-Arrestins have been reported to be involved in motility of SMCs. 41 We found that silencing of b-arrestin2 with siRNA transfection in SMCs ( Figure S3A) markedly reduced the phosphorylation of mTOR and p70S6K induced by BW723C86 ( Figure 5B). These studies suggested that b-arrestin2 played a critical role in the 5-HT2BR-mediated activation of the mTOR/p70S6K pathway in SMCs.…”
Section: -Ht2br Stimulated the B-arrestin2-mtor/ P70s6k Signalingmentioning
confidence: 85%
See 2 more Smart Citations